Meningkatkan Minat Belajar Menggunakan Buku Pop-Up Di Taman Pendidikan Qur'an Desa Mancilan - Airlangga, Primaadi; Chakim, Muhammad Abdul; Ya'la, Abu; Hasna, Afifatul; Devitasari, Afida (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The Baitul Muttaqin Quran Education Center, located in the Village of Mancilan Jombang, has approximately 160 students consisting of 4 study groups, which at this moment having problem where the students tend to be less interested on learning Al Quran and have difficulty learning Al Quran. The reason for the decline in enthusiasm for religious learning is due to the increase in study time at formal schools and the increase of time they used on playing with smartphones which has a negative impact on the desire and ability to spend their time reading and writing Al Quran verse. This is the basis for carrying out community service using a CSR approach starting from socializing a learning media using Pop-Up book, training on how to make pop-up book, mentoring the process of participants making pop-up book which is fun and interesting. So that it can increase interest in learning at TPQ Baitul Muttaqin